Schooling Islam The culture and politics of modern Muslim education - Hefner, Robert W. 1952- (Princeton studies in Muslim politics, 2007)
Main description: Since the Taliban seized Kabul in 1996, the public has grappled with the relationship between Islamic education and radical Islam. Media reports tend to paint madrasas--religious schools dedicated to Islamic learning--as medieval institutions opposed to all that is Western and as breeding grounds for terrorists. Others have claimed that without reforms, Islam and the West are doomed to a clash of civilizations. Robert Hefner and Muhammad Qasim Zaman bring together eleven internationally renowned scholars to examine the varieties of modern Muslim education and their implications for national and global politics. The contributors provide new insights into Muslim culture and politics in countries as different as Morocco, Egypt, Pakistan, India, Indonesia, Iran, and Saudi Arabia. They demonstrate that Islamic education is neither timelessly traditional nor medieval, but rather complex, evolving, and diverse in its institutions and practices. They reveal that a struggle for hearts and minds in Muslim lands started long before the Western media discovered madrasas, and that Islamic schools remain on its front line. Schooling Islam is the most comprehensive work available in any language on madrasas and Islamic education